IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING PADA AYAT MUTASHABIHAT AL ALFAZ - Merlyan Milania Fibria; Umi Kalsum (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2023)
Abstract: This study explores and analyzes the implementation of discovery learning learning models in learning tahfidz al-Quran at MI Al Kautsar Durisawo Ponorogo. This study aims to analyze the learning of tahfidz al-Quran which adopts kurikulum merdeka learning model, namely discovery learning, especially on mutashabihat al alfaz material. The resemblance of the verses in the Koran, which amount to more than 2000 verses, certainly has a level of difficulty for memorizers. From several stages of discovery learning it is very suitable to be implemented in verse mutashabihat al alfaz. The stimulation stage is carried out by the teacher asking questions about similar verses to students, the problem statement stage where students are given the opportunity to identify and analyze the problems they face, the fourth stage is data processing (data processing) to process data or information that students have obtained both through observing and looking for tashabuh verses in the Mushaf, The verification stage is that students carry out a careful examination to prove whether the hypothesis set is true or not by checking in the mutashabihat al al-alfaz books then Siwa draws conclusions and generalizations from the theory. Kata Kunci: Model Pembelajaran; Kurikulum Merdeka, Discovery Learning, Mutasha>biha>t Al alfaz} Abstrak: Penelitian ini menelusuri dan menganalis tentang implementasi model pembelajaran discovery learning pada pembelajaran tahfidz al Quran di MI Al Kautsar Durisawo Ponorogo. Penelitian ini bertujuan menganalisa pembelajaran tahfidzul Quran yang mengadopsi model pembelajaran kurikuum merdeka yaitu discovery learning terutama pada materi mutashabihat al alfaz. Kemiripan ayat dalam al Quran yang berjumlah 2000 lebih ayat tentunya mempunyai tingkat kesulitan bagi para penghafal. Dari beberapa tahapan discovery learning sangat sesuai untuk diimplementasikan pada ayat mutashabihat al alfaz. Tahapan stimulasi dilakukan dengan guru memberikan pertanyaan terhadap ayat yang mirip kepada siswa, Tahapan problem statement dimana siswa diberikan kesempatan untuk mengidentifikasi dan menganalisa permasalahan yang mereka hadapi, tahap keempat data processing (pengolahan data) mengolah data atau informasi yang telah diperoleh siswa baik melalui mencermati dan mencari tashabuh ayat dalam mushaf, Tahapan verfikasi yaitu siswa melakukan pemeriksaan secara cermat untuk membuktikan apakah hipotesis yang ditetapkan benar atau tidak dengan mengecek di kitab-kitab mutashabihat al alfaz kemudian siwa menarik kesimpulan dan generalisasi dari teori tersebut.